Central giant cell granuloma of the mandible: A perplexing case report - Roopashri Govindaraju; Archana Markande; Ruwena E Salins (Wolters Kluwer Medknow Publications, 2023)
Central giant cell granuloma is an eccentric jaw lesion that mystifies dental profession. Its pathogenicity remains a conundrum and requires differentiation from other similar lesions to develop an effective treatment plan. This case report reviews a case of central giant cell granuloma in a 52-year-old male who presented with a swelling on the right angle of mandible. The surgically curetted and reconstructed lesion resulted in the best esthetic and functional form with no recurrence during follow-up.